Efficacy of a web-based intervention for improving psychosocial well-being in patients with implantable cardioverter-defibrillators: the randomized controlled ICD-FORUM trial. (8th April 2019) - Schulz, Stefan M; Ritter, Oliver; Zniva, Richard; Nordbeck, Peter; Wacker, Christian; Jack, Mary; Groschup, Guido; Deneke, Thomas; Puppe, Frank; Ertl, Georg; Angermann, Christiane; Störk, Stefan; et al.
Abstract: Aims: Anxiety, depression, and reduced quality of life (QoL) are common in patients with implantable cardioverter-defibrillators (ICDs). Treatment options are limited and insufficiently defined. We evaluated the efficacy of a web-based intervention (WBI) vs. usual care (UC) for improving psychosocial well-being in ICD patients with elevated psychosocial distress. Methods and results: This multicentre, randomized controlled trial (RCT) enrolled 118 ICD patients with increased anxiety or depression [≥6 points on either subscale of the Hospital Anxiety and Depression Scale (HADS)] or reduced QoL [≤16 points on the Satisfaction with Life Scale (SWLS)] from seven German sites (mean age 58.8 ± 11.3 years, 22% women). The primary outcome was a composite assessing change in heart-focused fear, depression, and mental QoL 6 weeks after randomization to WBI or UC, stratified for age, gender, and indication for ICD placement. Web-based intervention consisted of 6 weeks' access to a structured interactive web-based programme (group format) including self-help interventions based on cognitive behaviour therapy, a virtual self-help group, and on-demand support from a trained psychologist. Linear mixed-effects models analyses showed that the primary outcome was similar between groups ( η p 2 = 0.001). Web-based intervention was superior to UC in change from pre-intervention to 6 weeks (overprotective support; P = 0.004, η p 2 = 0.036), pre-intervention to 1 year (depression, P = 0.004, η p 2 = 0.032; self-management, P = 0.03, η p 2 = 0.015; overprotective support; P = 0.02, η p 2 = 0.031), and 6 weeks to 1 year (depression, P = 0.02, η p 2 = 0.026; anxiety, P = 0.03, η p 2 = 0.022; mobilization of social support, P = 0.047, η p 2 = 0.018). Conclusion: Although the primary outcome was neutral, this is the first RCT showing that WBI can improve psychosocial well-being in ICD patients.